A Review of Commercially Available Point-of-Care Devices to Concentrate Bone Marrow for the Treatment of Osteoarthritis and Focal Cartilage Lesions. (October 2019) - Gaul, Florian; Bugbee, William D.; Hoenecke, Heinz R.; D'Lima, Darryl D.
Objective: Mesenchymal stem cells (MSCs) are a promising cell-based therapy treatment option for several orthopedic indications. Because culture expansion of MSC is time and cost intensive, a bedside concentration of bone marrow (BM) aspirate is used as an alternative. Many commercial systems are available but the available literature and knowledge regarding these systems is limited. We compared different point-of-care devices that concentrate BM (BMC) by focusing on technical features and quality parameters to help surgeons make informed decisions while selecting the appropriate device. Methods: We compared published data on the BMC devices of Arteriocyte, Arthrex, Celling Biosciences, EmCyte, Exactech, ISTO Tech, Harvest Tech/Terumo BCT, and Zimmer/BIOMET regarding technical features (centrifugation speed/time, input/output volume, kit components, type of aspiration syringes, filter usage) and quality parameters of their final BMC product (hematocrit, concentration of platelets and total nucleated cells, concentration of MSC and connective tissue progenitor cells). Results: The systems differ significantly in their technical features and centrifugation parameters. Only the fully automated systems use universal kits, which allow processing different volumes of BM. Only the Arthrex system allows selection of final hematocrit. There was no standardized reporting method to describe biologic potency. Conclusions: Based on the data obtained in this review, recommending a single device is not possible because the reported data could not be compared between devices. A standardized reporting method is needed for valid comparisons. Furthermore, clinical outcomes are required to establish the true efficacy of these systems. We are conducting additional studies for more careful comparison among the devices.